2023
DOI: 10.5114/biolsport.2023.118023
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of flight time and countermovement-jump height estimated from videos at different frame rates with MyJump

Abstract: Recent improvements in smartphone video technology may provide sufficient accuracy for estimation of jump height via flight time determined from video recordings of vertical-jump tests. The aim of this study is to evaluate the accuracy of jump height estimated from videos at different frame rates. High-definition videos of 10 young adults (6 males, 4 females) performing 5 countermovement jumps were recorded at a frame rate of 1000 Hz and transcoded to frame rates of 120, 240, and 480 Hz. Flight time in the vid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
(43 reference statements)
0
4
1
Order By: Relevance
“…However, when the results of Rater 3 were removed, the absolute agreement between the expert raters was excellent . These findings contrast with a study by Pueo et al (33), who found no difference in reliability between trained and untrained raters when measuring jumps on firm ground, highlighting the challenges of measuring jumping performance on sand surfaces. Still, with the help of an adequate protocol for takeoff and landing detection, MyJump2 provides reliable results, highlighting the applicability of coaches to obtain data on sand surfaces.…”
Section: Discussioncontrasting
confidence: 99%
“…However, when the results of Rater 3 were removed, the absolute agreement between the expert raters was excellent . These findings contrast with a study by Pueo et al (33), who found no difference in reliability between trained and untrained raters when measuring jumps on firm ground, highlighting the challenges of measuring jumping performance on sand surfaces. Still, with the help of an adequate protocol for takeoff and landing detection, MyJump2 provides reliable results, highlighting the applicability of coaches to obtain data on sand surfaces.…”
Section: Discussioncontrasting
confidence: 99%
“…At the same time, one of the main disadvantages of this application is that it requires the user to visually select the video frames of the takeoff and landing moments, which may lead to an interrater disagreement and thus potentially inaccurate results. However, a recent study showed good agreement between trained and untrained raters for jump height assessment, indicating that the video application has good interrater reliability (44).…”
Section: Introductionmentioning
confidence: 99%
“…Reliability of the instrument has been analyzed in a test–retest design in various studies [ 54 ]. For Vmaxpro , reliability on the hip was determined to be similar (ICC = 0.98; CV = 6.1%) compared to other studies where the device was placed on the hip (ICCs range: 0.86 to 0.98; CVs range: 3.1% to 10.7%) [ 15 , 16 , 19 , 21 , 55 ]. Placing the IMU on the forefoot showed better reliability figures (ICC = 0.89 to 0.90; CV = 4.1% to 4.3%) [ 18 , 56 ] than the Vmaxpro on the ankle in this study (ICC = 0.79; CV = 8.1%).…”
Section: Discussionmentioning
confidence: 90%
“…These factors can be so significant that they might mask the variability of the instrument. To mitigate this, averaging multiple jumps in the data analysis instead of using raw data can help avoid uncertainty [ 55 ].…”
Section: Discussionmentioning
confidence: 99%